The Read–Cover–Remember–Retell (RCRR) Technique in Enhancing EFL Learners’ Reading Comprehension: A Lesson from Junior High School Context - Agusriani, Agusriani; Munir, Syahrul; Agussatriana, Agussatriana (Journal of Language and Literature Studies, 2025)
This study investigates the effectiveness of the Read–Cover–Remember–Retell (RCRR) technique in enhancing EFL learners’ reading comprehension of narrative texts in a junior high school context. The research was conducted with ninth-grade students of SMP Negeri 15 Palu using a quasi-experimental design involving two intact classes. One class was assigned as the experimental group, taught using the RCRR technique, while the other served as the control group and received conventional reading instruction. Data were collected through pre-test and post-test reading comprehension assessments consisting of multiple-choice items that measured students’ ability to identify main ideas, supporting details, vocabulary meaning, and inferences. Descriptive statistics were used to examine students’ initial and final performance, and an independent samples t-test was employed to determine the significance of differences between the two groups. The results showed that the experimental group’s mean post-test score increased substantially compared to its pre-test score and outperformed the control group, which demonstrated only modest improvement. The statistical analysis confirmed that the difference between the post-test scores of both groups was significant, indicating that the RCRR technique had a positive impact on students’ reading comprehension. The findings suggest that the structured stages of RCRR promote active engagement, deeper processing of textual information, and better recall, making reading a more interactive and meaningful activity. This study concludes that RCRR is an effective and practical strategy for improving reading comprehension in EFL classrooms and offers pedagogical implications for teachers seeking student-centered approaches aligned with curriculum demands.